Variations of residual trihalomethane concentration in pipe-borne water during different in-house practices. Issue 3 (7th March 2023) - Jayasinghe, Nepali Sewwandi; Herath, Dilini Chandima; Weerasekara, Lalith Indranath; Weragoda, Sujithra Kaushalya; Amarasooriya, A. A. Gayan Darshana
Abstract: This study was conducted to investigate the effect of different in-house practices on trihalomethane (THM) level fluctuations in pipe-borne water. Common in-house practices such as boiling, unboiling, boiling water with headspace/non-headspace, storage vessels materials, storage practices, and storage time were investigated to study residual THM and their percentage. Vessels made of plastic (P), clay (C), stainless steel (SS), glass (G), and aluminium (Al) were used for the study. Prime trihalomethanes of CHCl3, CHBrCl2, CHBr2 Cl, CHBr3, and total of those four THMs (TTHMs) were measured, and removal/formation percentages were calculated. Results revealed that the percent change of TTHM varies based on the boiling practice as follows: open boiling TTHM > close boiling with headspace TTHM > close boiling without headspace (CBWH) TTHM. The following order was observed for residual TTHM for 6 h storage in the vessels; for CBWH water storage in open vessels C < G < P < SS < Al and close vessels C < G < P < SS < Al; and for unboiled water storage in open vessels SS < C < Al < P < G and close vessels C < P < Al < SS < G. In conclusion, the lowest concentration of residual TTHM was found in the boiled water stored in a clay pot and recommended as an in-house practice to reduce TTHM. HIGHLIGHTS: It is important to the South Asian community especially who lives in countries which apply chlorine for drinking water purification. This is the first study about trihalomethane (THM) variations with storage practices in Sri Lanka. It is an initiation of a good household practice. Excessive THM could adversely impact health. Emphasize the importance of using clay pots for drinking water storage. Graphical Abstract